Analisis Manajemen Kinerja dalam Penataan Tenaga Non-ASN oleh Kementerian PANRB - Uswatun Nur Auliya; Raihani Khairunissa Barni; Ayu Maulani; Luninda Hamidah Pasya; Muhammad Khoirul Anwar (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Bureaucratic reform is an essential step in realizing a clean, accountable, professional, and transparent government. The 2020–2024 Bureaucratic Reform Road Map has emphasized the Ministry of Administrative and Bureaucratic Reform’s (Kementerian PANRB) efforts to establish a healthy bureaucracy through the strengthening of the merit system, performance management, and service digitalization. As providers of public services, Civil Servants (ASN) play a crucial role in ensuring professional public service delivery; therefore, an organized performance management system is required to achieve optimal bureaucratic reform. However, in practice, the performance management implemented by the Ministry still faces challenges, particularly concerning non-ASN personnel. This study aims to analyze the implementation of performance management in the process of structuring non-ASN personnel by the Ministry of PANRB as part of the national bureaucratic reform agenda. The research employs a qualitative approach with descriptive analysis based on literature review, legislation, and secondary data from official sources. The findings indicate that the policy of structuring non-ASN personnel, grounded in the principles of the merit system and performance management, has brought significant changes to human resource governance within government institutions. Nevertheless, its implementation still encounters challenges such as limited budget allocation, lack of integrated performance data, and uncertainty regarding the employment status and welfare of non-ASN employees. The digitalization efforts through the e-Kinerja system and national personnel data collection serve as strategic steps to enhance transparency and accountability in performance assessment. Thus, comprehensive performance management is expected to promote professionalism among public servants, improve organizational effectiveness, and realize an adaptive and integrity-based bureaucracy.